The Oxford handbook of Asian business systems - Witt, Michael A.; Redding, S. G. (Oxford : Oxford University Press, 2013)
This handbook explores institutional variations across the political economies of different societies within Asia. It includes empirical analysis of 13 major Asian business systems between India and Japan, and examines these in a comparative, historical, and theoretical context.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on February 26, 2014).
Keywords: Industrial management -- Asia; Asia -- Commerce